Morfologia, Farmacologia e Fitoquímica foliar de Erythroxylum campestre A. St. -Hil. e Erythroxylum. deciduum A. St. -Hil. (Erythroxylaceae) - Safadi, Giuliana Muniz Vila Verde (2011)
The genus Erythroxylum belonges to the family Erythroxylaceae, wich is presented by four genera and 130 species occurring in tropical and subtropical the world. How has the best known, Erythroxylum coca Lam. is an important source of tropane alkaloids such as cocaine. Thus, this paper describes in article form, the morphological, pharmacological and phytochemical studies of the leaf from two Cerrado’s species, as the Erythroxylum campestre A. St. Hil. and Erythroxylum deciduum A. St. Hil. The article 1 deals with both morphoanatomical species, which can perfectly be used as parameters of differentiation between them. In cross section the characteristics that vary more between species were: outline of the main vein, so the system vascular in midrib and petiole; cuticle with or without ornamentations; epicuticular wax; shaped crystals of druse, which may occur in the epidermis, the pith of the main vein and between veins of smaller caliber, ratios of intercellular spaces in parenchyma. Papillary cells were observed, sclereids in E. campestre. In histochemical analysis, lipophilic compounds, compounds phenolics, starch in virtually all tissues of the leaf blade. In article 2, we determined the standards for purity and integrity a drug of the two species as well as the profiles were determined chemicals. It was observed the presence of flavonoids, tannins and resins in E. campestre, and triperpenos, alkaloids, flavonoids and tannins in E. deciduum. Article 3 deals with the General and specific pharmacological evaluation of crude ethanol extract of species, used in doses of 100, 300 and 1000 mg / kg. In test pharmacological activity generally observed behaviors challenging, followed by depression for E. deciduum, being on the rota rod test and time activity test of barbiturate-induced sleep, both extracts no significant effect. In the open field, there was motor impairment caused by E. deciduum extract, inhibiting the locomotion animals in 37% and no meaningful action to E. campestre extract. Yet the production of fecal material from animals treated with E. country was significantly increased from 3.0 ± 6.0 and E. deciduum decreased 3.5 ± 0.5.These studies suggest further research on the action laxative E. campestre and motor impairment of E. deciduum. In article 4, the evaluation of essential oils identified 34 compounds for both species, and these are phenylpropanoids 4.76%, 38.09% of sesquiterpenes, 33.33% of monoterpenes. Of these, only 4 are common between both species. Although, we evaluated the composition of the soil, where species were collected, because it is known that there is an impact on production secondary metabolites. The soil has dystrophic character (V ≤ 50%) and moderately acid (pH = 5.3), low cationic exchange capacity, and calcium and manganese and potassium ions as the predominant complex exchanges soil. This paper is an initial contribution to the studies of a genus whose species are found in a wide diversity in Cerrado of Goiás and it deserves attention.